Can the internet based intervention ‘strategies for empowering activities in everyday life’ support people with cognitive difficulties to self-manage digital work and everyday life? - Monika Lindberg; Maria Ranner; Lars Jacobsson; Eva Månsson Lexell; Maria Larsson-Lund (Scandinavian Journal of Occupational Therapy)
Background Digital work can be cognitively challenging especially for people with cognitive difficulties. New occupational therapy interventions are needed to empower these persons to self-manage challenges in digital work and everyday life. To address this need, the internet-based intervention ‘Strategies for Empowering Activities in Everyday Life’ (SEE 2.0) was tested.Aim To explore and describe how SEE can support the development of self-management in people with cognitive difficulties who engage in digital work and other occupations in everyday life.Material and methods A qualitative, descriptive case study included four participants with cognitive difficulties due to neurological disorders who participated in SEE. Data were collected through semi-structured interviews, self-reports and assessments then analysed using pattern matching.Results Three cases were formed. Two cases (three people) adhered to SEE’s intervention process, resulting in increased work hours, improved occupational balance, and greater engagement in valued occupations. One case (one person) could not fully adhere to the process and struggled to adopt changes.Conclusions SEE shows potential in supporting self-management, promoting sustainable digital work and everyday life.Significance SEE can add to existing vocational rehabilitation programs by empowering persons to utilise their own resources to manage challenges in everyday life.